Knowledge and Practice of Face Mask Use and Handling during COVID-19 Pandemic among Dental Students and Intern at B.P. Koirala Institute of Health Sciences - Keshwar, Shashi; Jain, Neetu; Sarraf, Deependra Prasad; Shrestha, Ashish (Journal of BP Koirala Institute of Health Sciences, 2023)
Background: The outbreak of Corona Virus Diseases (COVID-19) has been deemed a global public health emergency by the World Health Organization (WHO). Face mask is one of the prevalent used methods to reduce the spread of infection. Due to their widespread use, it is crucial to use these masks properly because improper use or disposal could potentially speed up the pace of transmission. The objective was to assess the knowledge and practice of face mask use and handing in undergraduate dental students.Methods: A web based cross sectional study was conducted among BDS third, fourth, fifth year and interns at College of Dental Surgery, B. P. Koirala Institute of Health Sciences between May-June 2021. A structured proforma was prepared and modified based on relevant literature and expert’s advice. The Google Forms with questionnaires were created using docs.google.com/forms, and the link was shared with the signed-up participants via messaging apps Viber and WhatsApp. Statistical Package for the Social Sciences software, version 21 was used to analyse descriptive statistics such as frequency and percentage.Results: A total of 144 participants responded to the questionnaire. Eighty-five (59.03%) participants responded that minimum numberof layers in face mask that work better to help stop the spread of COVID-19 outside health care setting is three. Sixty-seven (46.53%) participants responded that they touch front surface of the face mask while wearing it.Conclusion: Campaigns to raise awareness about the proper use of face masks during this pandemic will be useful in educating dentistry students and interns.